Ergonomic Risk Level of Work Posture in Leather Shoes Industry - Ekawati, Ekawati; Setyaningsih, Yuliani; Kurniawan, Bina; Wahyuni, Ida (Universitas Islam Bandung, 2024)
Posture while working will influence work results and have a health impact on workers. Rapid upper limb assessment (RULA) is a method for analyzing work posture on the job using the upper part of the body. This research examines the risk level of work postures in the leather shoe industry. This research was conducted in the leather shoe industry located in Semarang. This research uses the RULA method to assess the risk level of work postures. Body area measured by RULA was divided into two groups, namely group A (arms, forearms, hands) and group B (neck, body). The RULA score is obtained based on observing the worker's body posture, including neck, arms, back, legs, and load. The observed scores are then converted into final RULA scores. It was found that the body posture of workers in the leather industry was at a score of 6 and 7. This score has implications for the need for further research regarding the body posture of the following workers. Work posture correction must be done immediately to prevent further health impacts.